Increased circulating platelet microparticles as a potential biomarker in asthma. Issue 8 (29th July 2013) - Duarte, D.; Taveira‐Gomes, T.; Sokhatska, O.; Palmares, C.; Costa, R.; Negrão, R.; Guimarães, J. T.; Delgado, L.; Soares, R.; Moreira, A.
Abstract: Background: Endothelial (EMPs) and platelet microparticles (PMPs) have been studied as biomarkers in several inflammatory diseases and as central players in intercellular communication. Methods: In this cross‐sectional study, we aimed to assess microparticle levels in asthma. Circulating microparticles and inflammatory and angiogenic markers were assessed by clinical and laboratorial evaluation, flow cytometry, and immunoassays, in a group of 20 asthmatic and 15 nonasthmatic subjects. Results: Circulating levels of PMPs (either CD31+/42b+ or CD31+/42b+/AnV+) were significantly increased in asthmatics ( P  = 0.021) even after adjustment for confounders. Apoptotic EMPs (CD31+/42b−−/AnV+) were significantly increased before ( P  = 0.005) but not after adjustments ( P  = 0.117). Conclusions: We propose that PMPs may be putative asthma biomarkers, playing a role in asthma pathophysiology.